The Effect of Financial Performance, CSR, on Firm Value Through Managerial Ownership As a Moderating Variable In Food and Beverage Companies Listed on The BEI in 2020-2022 - Intan Devi Karimah; Yanuar Ramadhan (Green Publisher Indonesia, 2025)
This study aims to find empirical evidence regarding the effect of financial performance, corporate social responsibility on firm value with managerial ownership as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange for the period 2020-2022. The number of companies used as samples is 10 companies using purposive sampling method and secondary data obtained by the Indonesia Stock Exchange. The analysis used to test is multiple linear regression analysis with Moderated Regression Analysis (MRA) using the SPSS 24.0 program. The results of this study indicate that Financial Performance proxied by Return On Assets has an effect on Firm Value proxied by Tobins'Q, Corporate Social Responsibility has no effect on Firm Value proxied by Tobins'Q. Moderating Variable Managerial Ownership has no effect on Firm Value. Moderating Variables Managerial Ownership cannot moderate or weaken Financial Performance and Corporate Social Responsibility on Company Value.